Evaluating Students Acceptance of Google Classroom in Co-Curricular Photography Course Using Technology Acceptance Model (TAM): Evaluating Students Acceptance of Google Classroom in Co-Curricular Photography Course Using Technology Acceptance Model (TAM) - Wan Zuraida; Tengku Besaruddin Shah Tengku Yaakob; Noniwati Ahmad (International Journal of Technology Vocational Education and Training, 2023)
The purpose of this study is to evaluate the factors that affect Google Classroom (GC) acceptance among student’s photography courses in Politeknik Sultan Haji Ahmad Shah (POLISAS). The framework of the study is based on the Technology Acceptance Model. This study attempts to evaluate is there any significant relationship between1) perceived ease of use (PEOU) with perceived usefulness (PU) of GC usage? 2) perceived ease of use (PEOU) with behavioral intention (BI) to use GC usage? and 3) perceived usefulness (PU) with behavioral intention (BI) to use GC usage? The populations are 35 students who enrolled in the Photography course in June 2019 Session where GC is being applied as a teaching and learning (TnL) tool. 29 samples are collected based on simple random sampling. The Partial Least Square-Structural Equation Modeling approach was used to determine the hypothesis model. Cronbach’s Alpha coefficient and Composite Reliability are used to determine the internal consistency reliability with the value > 0.8. The Factor Loading is > 0.5 with the range from 0.701 to 0.939 for convergent validity. Discriminant validity for HTMT is met with the value of constructs < 1. The results revealed that there is a significant relationship between PEOU with PU of GC usage, PEOU positively affects BI for students’ in the POLISAS photography club to use GC and the result indicates that there is no significant relationship between PU with BI to use GC. Further efforts and improvements should be done to student’s attitudes and behavior in applying TnL methods.